Changes in the onset and intensity of wind‐driven upwelling and downwelling along the North American Pacific coast. Issue 5 (22nd May 2013) - Bylhouwer, Brian; Ianson, Debby; Kohfeld, Karen
Abstract : [1] The timing, duration, and intensity of wind‐driven upwelling and downwelling along the North American Pacific coast play an integral role in coastal circulation and basinwide ecosystem composition. It has been suggested that global warming will cause changes in these winds. Here we develop a new set of objective criteria to unambiguously determine the onset, duration, and intensity of upwelling and downwelling seasons due to local wind forcing. We use these criteria to examine and better characterize temporal trends in wind‐driven coastal currents over the previous 60 years and relate them to global warming and large‐scale climate oscillations in the coastal ocean between northern California and Vancouver Island (37°N and 51°N). We find an exceptionally variable onset of upwelling at all locations. Some significant temporal trends are found in summer onset and upwelling intensity time series near the Juan de Fuca Strait and off the coast of Oregon. Positive phases of the Pacific Decadal Oscillation are correlated to later and shorter upwelling seasons with weaker upwelling. Warm phases of the El Niño Southern Oscillation are associated with a later onset of summer upwelling south of Oregon and with more intense downwelling throughout the study area. Our analysis identifies strong interannual to interdecadal variability, and emphasizes the importance of time series length when isolating physical temporal trends influenced by large‐scale oscillatory behavior of the climate. Key Points: Onset and duration of up and downwelling can be determined from local winds Temporal trends in onset and intensity of upwelling depend on time series length Season onset, duration and intensity is highly variable in northern CCS